A repercussão geral no recurso extraordinário: mitigação dos requisitos formais - Monteiro, Dáfini de Araújo Perácio (2010)
The present work aims to study the institution of general repercussion, introduced into our legal system by Constitutional Amendment No. 45. To enable this study, we performed a similar institute analysis, the changes brought to the trial of extraordinary appeal and practical issues related to the topic. We dealt with controversial issues such as the dismissal of resources over the same dispute, inability to appeal the decision decreed that the lack of general repercussion, amicus curiae participation, among other situations created by the new law. The conclusion reached in the present study was that the general repercussion is a viable tool to select the causes that really matter, they deserve the trial by the Supreme Court. Should then be the main basis for selection of causes